Putin redux - Sakwa, Richard., author.
1 online resource (viii, 254 pages)
Keywords: "This book builds on the strengths of the previous volumes by the same author to provide the most detailed and nuanced account of the man, his politics and his profound influence on Russian politics, foreign policy and society. However, this is not a new edition of the earlier books but is an entirely new work. The focus now is on the dilemmas of power since 2008. There is a brief biographical sketch of Vladimir Putin and much analysis of his ideas and policies, but the book now focuses on the systemic contradictions that have created a blockage on modernisation and a stalemate in politics, Putin's role as Prime Minister since 2008 and his political successes and failures, analysis of the implications of Putin's third term as President and the 2011-12 electoral cycle and the ensuing crisis which led to thousands protesting on the streets This work assesses the achievements and failing of Putin's rule, but above all tries to make sense of contemporary developments. This is the definitive account of Putin and is essential reading for all scholars and students of Russian politics"--